THE FREQUENCY OF INFECTIONS WITH UREAPLASMA UREALYTICUM AND MYCOPLASMA HOMINIS AND THEIR CORRELATION WITH POSITIVE RESULTS FOR CANDIDA SPECIES IN PREGNANT AND NON-PREGNANT WOMEN - Mihajlović, Dejan; Ilic, Aleksandra; Minić, Verica; Milentijević, Milica; Dunjić, Momir (Acta medicae Medianae, 2024)
Mycoplasma hominis, Ureaplasma urealytium and Candida species (Candida spp.) are potentially pathogenic strains of microorganisms that can often be found in the genital tract of healthy women. However, the mentioned strains with additional factors can lead to numerous complications. The research aimed to determine the one-year prevalence of infection with Mycoplasma and Ureaplasma in pregnant and non-pregnant patients, as well as the correlation of infection with Candida spp. The study included 206 outpatients 30.8 ± 7 years of average age treated for symptoms of vaginal infection at the Department of Gynaecology and Obstetrics of the Clinical Hospital Center of Kosovska Mitrovica. All patients were tested for Mycoplasma and Ureaplasma by taking a standard vaginal and cervical smear. Cultures were seeded according to standard protocols. Out of 206 patients, 71 were pregnant. A positive test for Mycoplasma was found in 32 patients, Ureaplasma in 96, and 52 patients in the entire sample had vaginal candidiasis. Six pregnant women were positive for Mycoplasma and 29 for Ureaplasma. Vaginal candidiasis was significantly more common in pregnant patients compared to non-pregnant patients (n = 40, p = 0.046). Ureaplasma infection was associated with candidiasis in 33 patients (p = 0.005). Almost half of the patients (46.6%) tested positive for Ureaplasma. In pregnant women, the most common infection was with Candida spp. Ureaplasma infection was often associated with vaginal candidiasis in the entire sample, and one should be careful in the treatment of these infections and rationally use antibiotics in correlation with the clinical findings with preventive use of vaginal antimycotics.
Keywords: Ureaplasma urealyticum, Mycoplasma hominis, Candida species, cervicitis, colpitis